SYNTHESIS OF SOME NEW HETEROCYCLIC COMPOUNDS FROM 2-AMINOBENZHYDRAZIDE - Hassan, Dheefaf F (Al-Nahrain Journal of Science, 2010)
Aminobenzhydrazide (1) was used as a precursor for preparation of some new heterocycliccompounds and Schiff bases (2-9). Also, derivatives containing thiadiazole, oxadiazole and triazolerings were prepared by treating compound (1) with phenyl isothiocyanate (10-13). The structure ofthese compounds were characterized from there melting point, FTIR spectroscopy and elemental analysis (